(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Every operation in a modern organization relies heavily on timely and accurate information to survive in today’s competitive market. This study seeks to analyze a techno-economic view of the ERP software implementation. The study will also examine the usefulness of the ERP system’s functionality assessment, effective use of Enterprise Resource Planning for achieving cost effectiveness in all organizational processes, and for supporting the knowledge management functions from the Indian Multinational Companies’ perspective. The main advantage of this approach is that the costs and benefits will be quantified and this makes it possible to use this information in combination with other quantitative evaluation models.